Micro‐RNAs in the aqueous humour of patients with diabetic macular oedema. (27th March 2020) - Cho, Heeyoon; Hwang, Mina; Hong, Eun H.; Yu, Hyoseon; Park, Hyun‐Hee; Koh, Seong‐Ho; Shin, Yong U.
Abstract: Importance: Micro‐RNAs (miRNAs) have been studied as new biomarkers or mediators in various diseases, but the value of aqueous humour (AH) miRNAs in diabetic macular oedema (DMO) is still not known. Background: To compare AH miRNAs and related cytokine expression in DMO patients and healthy controls. Design: Prospective cross‐sectional study. Participants: Twenty naïve DMO patients and 13 control subjects, who were scheduled for intravitreal injection and cataract surgery, respectively. Methods: AH samples were collected at the beginning of each procedure and analysed using a miRNA polymerase chain reaction (PCR) array composed of 84 miRNAs, reverse transcripase‐quantitative PCR (qPCR) for verifying selected differentially expressed miRNAs, and a cytokine assay, the results of which were compared with bioinformatics conducted to find out genes associated with DMO‐related miRNAs. Main Outcomes Measures: AH expression of miRNAs and cytokines and the bioinformatics results. Results: Five miRNAs (hsa‐miR‐185‐5p, hsa‐miR‐17‐5p, hsa‐miR‐20a‐5p, hsa‐miR‐15b‐5p and hsa‐miR‐15a‐5p) showing a fold change greater than −50 in log2 values in the miRNA PCR array were selected, all significantly down‐regulated in the DMO group compared to the control group ( P < .05), and showed a direct relationship with tumour necrosis factor, nuclear factor kappa B subunit 1 and interleukin‐6 (IL‐6) in bioinformatics analysis, all of which were related to vascular endothelial growth factor (VEGF). In the cytokine assay, the aqueous concentrations of VEGF, placental growth factor, IL‐6 and IL‐8 were significantly higher in the DMO group compared to the control group. Conclusions and Relevance: This study is the first to perform miRNA profiling of the AH of DMO patients. We identified differentially expressed miRNAs in DMO AH, which may be used as potential biomarkers or novel therapeutic targets for DMO.